3. Rewrite the expression with a single base and exponent. (3 to the 2nd power x 3 to the 3rd power) to the 3rd power

1 answer

3 to the 2nd power x 3 to the 3rd power = 3^2 x 3^3 = 3^(2+3) = 3^5
(3 to the 2nd power x 3 to the 3rd power) to the 3rd power = (3^5)^3 = 3^(5*3) = 3^15
Similar Questions
    1. answers icon 1 answer
  1. You rewrote the expression as 103 ·5. Can you rewrite 10 3 ·5 using a single base raised to a power? In other words, can you
    1. answers icon 1 answer
  2. Use the power of power rule to rewrite each expression as a single exponent1. ((-4)^-5)^-4 2.(8^3)^16 3. ((-2.3)^7/^2 4.((-
    1. answers icon 2 answers
    1. answers icon 1 answer
more similar questions